Modulating Diffusion-Weighted Magnetic Resonance Imaging for Screening in Oncologic Tertiary Prevention: A Prospective Ex Vivo and In Vivo Study. Issue 11 (November 2019) - Dreher, Constantin; Kuder, Tristan Anselm; König, Franziska; Paech, Daniel; Tavakoli, Andrej; Laun, Frederik Bernd; Flothow, Florian; Gnirs, Regula; Benkert, Thomas; Nickel, Dominik; Strecker, Ralf; Schlemmer, Heinz-Peter; et al.
Abstract : Introduction: Diffusion-weighted imaging (DWI) is an important part of oncological magnetic resonance imaging (MRI) examinations, especially for tertiary cancer prevention in terms of early detection of recurrent disease. However, abdominal studies can be challenged by motion artifacts, poor signal-to-noise ratios, and visibility of retroperitoneal structures, which necessitates sequence optimization depending on the investigated region. This study aims at prospectively evaluating an adapted DWI sequence ex vivo and in vivo in oncologic patients undergoing abdominal MRI. Methods: This institutional review board–approved, prospective study included phantom measurements, volunteer examinations, and oncologic patient examinations of the abdomen. Fifty-seven MRI examinations in 54 patients (mean age, 58 years; range, 21–90 years) were included into the analysis. The MRI examination were performed at a 1.5 T MRI scanner (MAGNETOM Aera; Siemens Healthcare, Erlangen, Germany) and included both a standard EPI-DWI (s-DWI; b = 50, 900 s/mm 2 ) and an adapted DWI (opt-DWI; EPI-DWI with b = 0, 50, 900, 1500 s/mm 2, acquisition with higher spatial resolution and optimized processing for the abdomen including motion correction, adaptive image combination, and background suppression). For b = 900 s/mm 2, the ratio of signal intensity in the normal tissue and the standard deviation of the noise in the surrounding air was quantitatively calculated; image quality and tissue differentiation parameters were rated by 2 independent, blinded readers using a 5-point Likert scale. Statistics included Wilcoxon signed-rank test and kappa statistic ( P < 0.05/0.0125 after Bonferroni correction). Results: The DWI phantom demonstrated an optimized contour sharpness and inlay differentiation for opt-DWI. The apparent ratio of normal tissue signal/standard deviation of background noise at b = 900 s/mm 2 of the right/left hemiabdomen was significantly increased in opt-DWI (mean, 71.9 ± 23.5/86.0 ± 43.3) versus s-DWI (mean, 51.4 ± 15.4/63.4 ± 36.5; P < 0.001). Image quality parameters (contour sharpness and tissue differentiation of upper abdominal and retroperitoneal structures) were significantly increased in opt-DWI versus s-DWI ( P < 0.001). Interreader reliability test showed good agreement (kappa = 0.768; P < 0.001). Discussion: This study prospectively evaluated the potential of adapted DWI for screening in tertiary prevention of oncologic patients. An optimized DWI protocol with advanced processing achieved improved image quality in quantitative and qualitative analyses. Oncological optimization of DWI should be performed before its application in cancer patients to improve both screening and follow-up examinations, to better unleash the diagnostic potential of DWI.